Ecology, invasion history and biodiversity-driven management of the coconut black-headed caterpillar Opisina arenosella in Asia - Lu, Hui; Lyu, Baoqian; Tang, Jihong; Wu, Qiqi; Wyckhuys, Kris A. G.; Le, Khac Hoang; Chongchitmate, Patchareewan; Qiu, Haiyan; Zhang, Qikai (Frontiers in Plant Science, 2023)
The coconut black-headed caterpillar (BHC), Opisina arenosella Walker (Lepidoptera: Xyloryctidae) is an important herbivore of palm trees that originates in South Asia. Over the past decades, O. arenosella has spread to several countries in Eastern and Southeast Asia. BHC larval feeding can cause severe defoliation and occasional plant death, resulting in direct production losses (e.g., for coconut) while degrading the aesthetic value of urban and rural landscapes. In this review paper, we systematically cover taxonomy, bio-ecology, invasion history and current management of O. arenosella throughout Asia. Given that O. arenosella is routinely controlled with insecticides, we equally explore options for more sustainable management through agroecological and biodiversity-based tactics e.g., cultural control or biological control. Also, recent advances in chemical ecology have unlocked lucrative opportunities for volatile-mediated monitoring, mating disruption and mass-trapping. Substantial progress has been made in augmentation biological control, with scheduled releases of laboratory-reared parasitoids lowering BHC infestation pressure up to 95%. Equally, resident ants provide 75-98% mortality of BHC egg masses within the palm canopy. Biological control has been effectively paired with sanitary measures and good agronomy (i.e., proper fertilization, irrigation), and promoted through participatory farmer training programs. Our comprehensive listing of non-chemical preventative and curative tactics offer bright prospects for a more environmentally-sound, biodiversity-driven mitigation of a palm pest of regional allure.